2021
DOI: 10.1111/jgs.17128
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative functional status is associated with discharge to nonhome in geriatric individuals

Abstract: Introduction Discharging older individuals to rehabilitation facilities is associated with adverse outcomes, including readmission or increased mortality rate. As preoperative functional status is an important factor impacting patient outcome, we hypothesized that this would be associated with patient disposition to nonhome locations. Materials and Methods A retrospective analysis was performed using data from the 2013–2018 American College of Surgeons National Surgical Quality Improvement Program, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Importantly, this study only evaluated multivariable associations of frailty with mortality and not with other discharge dispositions which have previously been shown to serve as reliable surrogates for degree of functional status impairment at the conclusion of hospitalization. 25 Insofar as routine discharge disposition to home represents a favorable functional status and substantive recovery, a potential mechanistic explanation for the findings of our analysis includes underdeveloped microcirculation and decreased perfusion capacity as well as neuronal abnormalities in frail patients. The relationship Components of the mFI-11 were each assigned a value of "1" and summed for each patient to create a composite score (maximum value 11).…”
Section: Discussionmentioning
confidence: 85%
“…Importantly, this study only evaluated multivariable associations of frailty with mortality and not with other discharge dispositions which have previously been shown to serve as reliable surrogates for degree of functional status impairment at the conclusion of hospitalization. 25 Insofar as routine discharge disposition to home represents a favorable functional status and substantive recovery, a potential mechanistic explanation for the findings of our analysis includes underdeveloped microcirculation and decreased perfusion capacity as well as neuronal abnormalities in frail patients. The relationship Components of the mFI-11 were each assigned a value of "1" and summed for each patient to create a composite score (maximum value 11).…”
Section: Discussionmentioning
confidence: 85%
“…Hung et al [17] used NSQIP from 2013 to 2019 and found that geriatric patients (65 years and above) and patients who had a partially dependent preoperative functional status were discharged to rehabilitation facilities or nursing homes significantly more often than those with an independent functional status [17]. The presence of these preoperative factors therefore contributes to an increased length of stay.…”
Section: Discussionmentioning
confidence: 99%